Psychometric properties of the Jefferson Empathy Scale in four nursing student faculties - Víctor Pedrero Castillo; Aracelis Calzadilla-Núñez; Claudia Moya-Ahumada; Pilar Torres-Martínez; Pablo Castro Pastén; Víctor Patricio Díaz-Narváez (SciELO, 2021)
ABSTRACT Objective To evaluate the psychometric properties of the Jefferson Medical Empathy Scale, Spanish version (JSE-S), its factorial structure, reliability, and the presence of invariance between genders in the behavior of empathy levels among Chilean nursing students. Method Instrumental research design. The JSE-S was applied to 1,320 nursing students. A confirmatory factor analysis was used. An invariance study between genders was carried out. Descriptive statistics were estimated. Between genders, Student's T distribution was applied alongside a homoscedasticity analysis. The level of significance was α ≤ 0.05. Results The confirmatory factor analysis determined the existence of three dimensions in the matrix. The statistical results of the invariance tests were significant, and allowed comparison between genders. Differences were found between mean empathy values, as well as in some of its dimensions between genders. Conclusion The factor structure of empathy data and its dimensions is in correspondence with the underlying three-dimensional model. There are differences in empathy levels and their dimensions between genders, with the exception of the compassionate care dimension, which was distributed similarly. Women were more empathetic than men.